PEYRONIE'S DISEASE - Mirza, Masoom Raza; Saria, Maria Shabbir; Mumtaz, Tasir Ahmed (Journal of Ayub Medical College Abbottabad, 2006)
Peyronie's disease is an uncommon condition and authors have not seen it in their practice. This is our first experience which is reported here. Key Words: Peyronie's, Penile, Plaque